Qualitative and quantitative variations of the vaginal epithelium in Myocastor coypus bonariensis (coypu) during the estrous cycle - Felipe, A.E. (2022)
The aim of the present study was to characterize the qualitative and quantitative changes in the vaginal\nepithelium in the coypu (M. c. bonariensis) during the estrous cycle. A daily colpocytological evaluation\nwas performed in 36 females. Samples from three vaginal sections (cephalic, middle and caudal) were\nprocessed with routine histological techniques. The mean cycle duration was of 36.86 ± 10.52 days. The\ngreater thickness of the epithelium was observed in the proestrous and the smallest in the metestrous.\nVariations in epithelial thickness in each cycle stage for the different sampled regions showed nonsignificant differences in the estrous and proestrous. Differences were observed during the metestrous between the cephalic and middle and middle and caudal regions, and also during the diestrous, being the most significant between cephalic and middle regions. At metestrous, a significant decrease in the number of epithelial layers was observed in all the regions. At diestrous, differences were observed between cephalic and middle, and cephalic and caudal regions.\n